TINDAK PIDANA PADA KAPAL PELAYARAN RAKYAT YANG BERLAYAR TANPA SURAT PERSETUJUAN BERLAYAR - Aptimus Aptimus (JURNAL AKTA YUDISIA, 2025)
This study examines the juridical review of criminal offenses committed by traditional maritime vessels sailing without a Sailing Approval Letter (Surat Persetujuan Berlayar/SPB). The SPB is a mandatory state document functioning as an instrument to supervise ship seaworthiness in order to ensure maritime safety and security. However, in practice, violations are still frequently found and may endanger human safety and the marine environment. This research employs a normative legal method using statutory and conceptual approaches through library research. The findings indicate that sailing without an SPB may result in criminal sanctions under Law Number 17 of 2008 on Shipping, with criminal liability imposed on the ship’s master when elements of fault are present. Effective law enforcement is therefore necessary to achieve safe and orderly maritime transportation.